Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0142255
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Post-Translational Modification Analysis of Leucine-Rich-Repeat Receptor-Like Kinases in Brassica rapa

Abstract: Among several receptor-like kinases (RLKs), leucine-rich-repeat receptor-like kinases (LRR-RLKs) are a major group of genes that play crucial roles in growth, development and stress responses in plant systems. Given that they have several functional roles, it is important to investigate their roles in Brassica rapa. In the present study, 303 LRR-RLKs were identified in the genome of B. rapa and comparative phylogenetic analysis of 1213 combined LRR-RLKs of B. rapa, Arabidopsis thaliana, Oryza sativa and Populu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
53
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 72 publications
14
53
1
Order By: Relevance
“…Hence, the results suggested LRR-RLK genes from different subfamilies and even genes from the same subfamilies exhibited expressional divergence. Similar results have also been obtained from the expression analyses of LRR-RLK genes from other plants (Zan et al, 2013; Rameneni et al, 2015; Wei et al, 2015; Shumayla et al, 2016; Zhou et al, 2016). …”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Hence, the results suggested LRR-RLK genes from different subfamilies and even genes from the same subfamilies exhibited expressional divergence. Similar results have also been obtained from the expression analyses of LRR-RLK genes from other plants (Zan et al, 2013; Rameneni et al, 2015; Wei et al, 2015; Shumayla et al, 2016; Zhou et al, 2016). …”
Section: Discussionsupporting
confidence: 78%
“…In this study, we focused on the number of LRR repeats in the LRR domain and motifs in the KD domain. Previous studies in eudicots and monocots reported that members within the same LRR-RLK subfamily tend to have a similar number of LRR repeats, whereas members of different subfamilies exhibit a different number of LRR repeats (Shiu and Bleecker, 2001; Sun and Wang, 2011; Zan et al, 2013; Rameneni et al, 2015; Wei et al, 2015; Magalhães et al, 2016; Shumayla et al, 2016). The protein structure analyses of LRR-RLK proteins in A. trichopoda reinforced the conclusion that the same subfamily members tend to have broadly the same number of LRR repeats in the LRR domain (Figures 3A,B and Table 1), while members of different subfamilies have different numbers of LRR repeats in the LRR domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brassica plants, genome-wide studies of LRR-RLKs and LRR-RLPs are limited. To date, only one study of LRR-RLK genes has been reported; in B. rapa (Rameneni et al, 2015). By contrast, genome-wide studies of nucleotide binding site-leucine-rich repeat (NBS-LRR) genes have been widely performed on several Brassica species, such as B.…”
Section: Introductionmentioning
confidence: 99%